Disrupting the consultation: students empowering patients in a longitudinal clerkship. Issue 6 (2nd November 2021) - McElhinney, Zoë; Bartlett, Maggie
ABSTRACT: Although well-established worldwide as a method of clinical medical education, Longitudinal Integrated Clerkships (LICs) are green shoots in the UK medical education landscape. The first comprehensive LIC in the UK was introduced in Dundee, Scotland in 2016. Substantial work has been carried out to evaluate the experiences of students and primary care tutors involved in the Dundee LIC, but the experiences of the patients LIC students cared for had not been evaluated. The purpose of this study was to explore the experiences of these patients, particularly the impact the involvement of a LIC student might have on their experience of healthcare. The study is a cross-sectional qualitative study involving semi-structured interviews with five patients who had experienced several contacts with LIC students. An interpretive phenomenological approach was taken. We describe the presence of the student as a disruptive force leading to the empowerment of patients. Students disrupted the status quo in the consultation by altering both the structure of the interaction and the doctor–patient relationship. The student–patient relationship was a powerful enabler of patient empowerment through the provision of education and information to the patient and through increasing patient centredness in the consultation. The positive social interaction provided by the student–patient relationship led to a reframing of patients' perceptions of the medical profession, challenging their perceptions of occupational hierarchy and power of the medical profession.